A chronic low dose of Δ9-tetrahydrocannabinol (3 mg / kg / 21 d) reorganizes the disturbed wound healing process and accelerates wound closure in old female mice - Melissa Plum; Justus P. Beier; Tim Ruhl (Experimental Gerontology)
Wound healing in old mice is characterized by disturbed tissue homeostasis, manifested by delayed immune cell infiltration and reduced growth factor secretion, leading to a delayed onset and prolonged duration of the inflammatory phase. The endocannabinoid system (ECS) is an important regulator of tissue homeostasis and cell migration and is also considered to be subject to aging processes, which may contribute to observable aging phenomena. Therefore, stimulating the aged ECS could represent a therapeutic option to support tissue regeneration in aging.Female old mice received a low-dose of medical THC daily for 3 weeks, before four excisional full skin wounds were created. At day 1, 3 and 7 post-surgery, the wound closure rate was analyzed and wound samples were examined immunohistochemically for the numbers of granulocytes, M1-macrophages and mesenchymal stem cells (MSCs). The concentrations of inflammatory cytokines and regenerative growth factors were determined by ELISA.Administration of THC improved the wound healing rate of old mice between day 1 and 7, which was associated with an altered timing and quantity of infiltrating immune cells and decreased levels of inflammatory cytokines in wound tissue on days 1 and 3 post-injury. THC treatment significantly increased MSC infiltration but had no effect on the growth factor release.The present study confirmed the anti-inflammatory activity of THC in vivo. The THC-treatment improved wound healing in old mice by coordinating the temporal sequence of immune cell infiltration and cytokine release. Thus, restoration of ECS signaling could be an effective strategy to support age-related skin regeneration.